Developing powers: modernization, economic development, and governance in Cold War Afghanistan - Nunan, T; Timothy Nunan (2013)
In the last decade, scholars have recognized economic development and modernization as crucial themes in the history of the twentieth century and the ‘global Cold War.’ Yet while historians have written lucid histories of the role of the social sciences in American foreign policy in the Third World, far less is known on the Soviet Union’s ideological and material support during the same period for countries like Egypt, India, Ethiopia, Angola, or – most prominently – Afghanistan. This dissertation argues that the Soviet intervention in Afghanistan is best understood as the final and most costly of a series developmental interventions staged in that country during the latter half of the twentieth century by Afghans, Soviets, Americans, Germans and others. Cold War-era Afghanistan is best understood as a laboratory for ideas about the nation-state and the idea of a ‘national economy.’ One can best understand Afghanistan during that period less through a common but ahistorical ‘graveyard of empires’ narrative, and more in terms of the history of the social sciences, the state system in South and Central Asia, and the ideological changes in ideas about the state and the economy in 20th century economic thought. Four chapters explore this theme, looking at the history of the Soviet social sciences, developmental interventions in Afghanistan prior to 1978, a case study of Soviet advisors in eastern Afghanistan, and Soviet interventions to protect Afghan women. Making use of new materials from Soviet, German, and American archives, and dozens of interviews with former Soviet advisors, this dissertation makes a new and meaningful contribution to the historical literature on the Soviet Union, Central Asia, and international history.